Lendo ficções para a vida: literatura, formação moral e emoções - Senhorinho, Jean Machado (2018)
This dissertation shows an investigation about how fictional literary works tout court can morally form us. The goal is to constitute a defense to literature potential for our moral formation. As starting point, the first chapter put forward an extensive reconstruction of John Gibson’s position in Fiction and the Weave of Life (2007). In this process, this work adopts Gibson’s treatments for two old philosophical deadlocks about literary art: the fictional one and the cognitive valor one. Summarily, first, the author employs the second Wittgenstein’s approach about language to clarify the direct connection between fictional texts and real world. Second, he advances a neocognitivist thesis to claims literary cognitive value in terms of “acknowledgement” and “understanding”, rather than “knowledge” and “true”. From Gibson’s philosophical vocabulary, in the second chapter, this work creates the “Moral Conceptuary Thesis” as an attempt to clarify how literature tout court can morally form us. According to this thesis, literature can evaluatively reorient our moral concepts; for instance, changing our moral understanding about life and our moral formation. Next, this work tests that proposal against empirical skepticisms and idealistic excesses about literature’s prospect for our moral education. The result of such consideration is a reservation about the current indeterminacy of literature’s moral influence level, frequency, and conditions upon us. The last chapter offers an additional qualification about the role of emotional engagement to adequate understanding of moral concepts. In this regard, the intention is to imply that emotions instigated for literature’s dramatic structure are crucial for morally oriented conceptual assimilation. At the end, for sake of exemplification, this study also brings a reading of Mary Wollstonecraft Shelley’s Frankenstein. This dissertation’s conclusion is that literature tout court has great potential to form us morally, notwithstanding the absence of reliable ways for the precision of such formative impact.